2022
DOI: 10.3390/reports5030027
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Obstetric Patient: Pregnancy Outcomes during COVID-19 Pandemic—A Single-Center Retrospective Study in Romania

Abstract: Acute respiratory-syndrome-related coronavirus 2, or SARS-CoV-2, has become a public health issue in our country. It mainly affects the vulnerable population, especially those with comorbidities. In this retrospective study, we set out to explore the effects of COVID-19 on pregnancy, with the vulnerability of pregnant women to SARS-CoV-2 infection also representing a main focus. We included 39 patients who tested positive for SARS-CoV-2 and 39 control subjects recruited from the Emergency County Hospital of Hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
(73 reference statements)
0
1
0
Order By: Relevance
“…According to current knowledge, pregnant women have an increased risk of developing severe pneumonia because they are more susceptible to respiratory pathogens due to changes in their immune systems [4]. A recent metaanalysis showed that black and Asian ethnicities, obesity, hypertension, and asthma are risk factors for developing COVID-19 related symptoms in pregnancy, although other authors report similar outcomes between COVID-19 positive and negative pregnant women, with complications (mostly bleeding or thrombosis) occurring only in a small percentage of COVID-19 cases [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…According to current knowledge, pregnant women have an increased risk of developing severe pneumonia because they are more susceptible to respiratory pathogens due to changes in their immune systems [4]. A recent metaanalysis showed that black and Asian ethnicities, obesity, hypertension, and asthma are risk factors for developing COVID-19 related symptoms in pregnancy, although other authors report similar outcomes between COVID-19 positive and negative pregnant women, with complications (mostly bleeding or thrombosis) occurring only in a small percentage of COVID-19 cases [5,6].…”
Section: Introductionmentioning
confidence: 99%